Impacts of State 4-H Council Service: A Phenomenological Study - Bradd L. Anderson (Journal of Human Sciences and Extension, 2021)
This qualitative study explored the experience of youth serving on the state 4-H council of Missouri, which provides opportunities to serve as ambassadors of the 4-H organization and influence the experiences of younger members. While many 4-H programs have a statewide youth council, there is little research regarding these groups or the impacts of state 4-H council service. This study employed a hermeneutic phenomenological approach to explore the impacts of State 4-H Council service among alumni, within a framework of positive youth development theory. Council service was found to have provided members experience in working with diverse others, created opportunities to expand relational networks, influenced individual actions, and affected changes in both individuals and their contexts.